2017
DOI: 10.1007/s12602-017-9278-6
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Strawberry Yogurts: Microbiological, Chemical and Sensory Properties

Abstract: This study was performed to determine the viability of Lactobacillus acidophilus and Bifidobacterium bifidum in yogurt made with strawberry marmalade (SM) and to examine the quality properties of probiotic yogurt. Acidity, pH, bacterial counts and sensory analysis of the yogurt samples were investigated on days 1, 3, 5, 7, 10 and 14 during storage at 4 °C. The survival rate of L. acidophilus was greater than that of B. bifidum. The viability of L. acidophilus decreased during the storage period, but B. bifidum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…Use of L. acidophilus alone in yogurt production (no GTP) strain lost viability and decay to <4 log cfu/g in the 28 th day. The L. acidophilus count was high up to the 7 th day, as previously also found by Turgut and Cakmakci [31] . However, the L. acidophilus count tended to decrease after the 7 th day of storage.…”
Section: Discussionsupporting
confidence: 87%
“…Use of L. acidophilus alone in yogurt production (no GTP) strain lost viability and decay to <4 log cfu/g in the 28 th day. The L. acidophilus count was high up to the 7 th day, as previously also found by Turgut and Cakmakci [31] . However, the L. acidophilus count tended to decrease after the 7 th day of storage.…”
Section: Discussionsupporting
confidence: 87%
“…Yogurt acidity during storage is a result of lactose fermentation (Tamime & Robinson, ) and affects the viability of L. acidophilus (Dave & Shah, ); therefore, the increased yogurt acidity during storage caused the decreased L. acidophilus counts. Similar results were reported by Akın and Güler‐Ak?n (2005) and Turgut & Çakmakçı ().…”
Section: Resultsmentioning
confidence: 99%
“…This study found a similar effect due to the Gobdin additive. Turgut & Çakmakçı () also found a similar effect from the sensory properties of control and probiotic yogurts. Güler‐Akın () and Akın & Güler‐Akın () determined which bio‐yogurts received higher scores than regular yogurt.…”
Section: Resultsmentioning
confidence: 99%
“…The expansion of milk products containing probiotic bacteria, as living microorganisms is a main subject in commercial and industrial impacts (Ghorbanzade, Jafari, Akhavan, & Hadavi, ). The most commercial and common probiotic bacteria are lactobacilli and bifidobacteria such as Bifidobacterium bifidum and Lactobacillus acidophilus (Turgut & Cakmakci, ). Many studies have been done to apply dairy products as carriers of Lactobacillus casei and bifidobacteria, like low‐acidity yogurts (Aliza Sigdel, Ojha, & Karki, ), cheese (Gandhi, Barrett‐Wilt, Steele, & Rankin, ), and yogurt (Turgut & Cakmakci, ).…”
Section: Introductionmentioning
confidence: 99%
“…The most commercial and common probiotic bacteria are lactobacilli and bifidobacteria such as Bifidobacterium bifidum and Lactobacillus acidophilus (Turgut & Cakmakci, ). Many studies have been done to apply dairy products as carriers of Lactobacillus casei and bifidobacteria, like low‐acidity yogurts (Aliza Sigdel, Ojha, & Karki, ), cheese (Gandhi, Barrett‐Wilt, Steele, & Rankin, ), and yogurt (Turgut & Cakmakci, ). The researchers suggested that the addition of common starter cultures such as Streptococcus thermophilus and Lactobacillus bulgaricus in obtaining products improved the typical numbers of probiotic bacteria, pH values, and sensory characteristics.…”
Section: Introductionmentioning
confidence: 99%